2016
DOI: 10.1093/jee/tow130
|View full text |Cite
|
Sign up to set email alerts
|

Essential Balm: A Strong Repellent Against Foraging and Defending Red Imported Fire Ants (Hymenoptera: Formicidae)

Abstract: In the present study, the repellent effects of essential balm, a traditional medicine product in China, was tested against foraging and defending red imported fire ants, Solenopsis invicta Buren, under laboratory and field conditions. The laboratory study showed that both band- (width = 1 cm) and patch-smearing of essential balm at each concentration (0.5, 1, or 2 μl/cm(2)) significantly decreased the number of S. invicta foragers within the 6-h observation period. Moreover, band-smearing of 2 μl/cm(2) essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
0
16
1
Order By: Relevance
“…In an earlier study essential balm repelled foraging S. invicta for 24 h in the laboratory 23 . In the present study, however, ants transported food away from seven of the eight squares smeared with essential balm at 24 h (Table S3).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In an earlier study essential balm repelled foraging S. invicta for 24 h in the laboratory 23 . In the present study, however, ants transported food away from seven of the eight squares smeared with essential balm at 24 h (Table S3).…”
Section: Discussioncontrasting
confidence: 52%
“…For example, Liu et al 22 reported that the fumigation treatment of essential balm can cause high mortality of storage pests such as Rhizopertha dominica (Fabricius), Cryptolestes pusillus (Schonherr), and Sitophilus zeamais (Motschulsky). Our earlier study showed that essential balm completely inhibited foraging behavior of five of six S. invicta colonies for 24 h. 23 This is the longest duration of repellency against S. invicta foragers reported. However, that was a laboratory study, and repellency has not been confirmed in the field.…”
Section: Introductionmentioning
confidence: 74%
“…Wang et al (2012) found that 1000 μl/mL of Capsicum annuum (sweet pepper) oil showed >90% repellent activity against S. invicta workers under laboratory conditions. Essential balm strongly repelled S. invicta workers even at the concentration of 0.5μL/cm 2 (Wen et al 2016). The repellence effect of two food additives, ethyl anthranilate and butyl anthranilate, were even better than diethyltoluamide (DEET) against S. invicta (Chen et al 2019b).…”
Section: Exploration For Control Methods Of S Invictamentioning
confidence: 98%
“…Using soil particles has been previously reported to be associated with foraging in S. invicta (Barber et al ., ; Hölldobler & Wilson, ; Weeks et al ., ; Xu et al ., ; Wang & Henderson, ; Wen et al ., ). The function of particle transport might vary with foraging conditions and food types.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Wen et al . () reported that S. invicta workers relocated a large number of soil particles on the substance treated with a repellent (essential balm). These particles, placed surrounding the food item, were used as bridges so that ants were able to reduce the contact with repellent chemicals and access the food.…”
Section: Discussionmentioning
confidence: 99%